Perlindungan Warga Negara Indoneisa di Luar Negeri Berdasarkan Hukum Internasional - Pipit Natalia; Rara Diah Pertiwi; Nur Hapipah; Muhammad Shidki; Budi Ardianto (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
The protection of citizens abroad has become an important issue in contemporary international law. Every country has an obligation to protect its citizens, both inside and outside its territory. However, the implementation of this protection often faces various challenges, especially related to state sovereignty and the principle of non-intervention in international law. This article aims to analyze the international legal basis regarding the protection of citizens abroad, as well as the practices carried out by countries in carrying out these protection obligations. The research method used is juridical-normative with a case study approach. The research results show that the protection of citizens abroad is based on the principles of international law, such as state responsibility, human rights and protection obligations. Countries have developed various mechanisms and legal instruments to realize the protection of their citizens, either through diplomacy, consular or other measures. However, its implementation still faces challenges related to the limitations of state sovereignty and the principle of non-intervention. This article concludes that the protection of citizens abroad is an international legal obligation that must be implemented by every country. Efforts are needed to strengthen the international legal framework and cooperation mechanisms between countries to ensure effective protection for their citizens abroad.